Language and Xenophobic Sentiments in South Africa - Ideh, Amaka Edith (NIU Journal of Social Sciences, 2022)
Cities are often subjected to external influences due to mass migration of people in search of better life. The migrants are sometimes faced with rejection by the host community, as they (the migrants) are often seen as competing for limited resources with their hosts. The xenophobic sentiments have motivated research on the problems encountered by immigrants in South Africa, which may include the impact of language of the media. This is because language is an embodiment of culture and an easy resource to access the community, as well as disseminate information. This study is set to explore the impact of language on xenophobic sentiment in South Africa with focus on Sesotho people in Bloemfontein. The exploration of the impact of language on anti-foreigner sentiments would help to identify the hidden power of the press in the dissemination of information in the society and how this information steers one’s mind and directly or indirectly controls it. The data for the study were collected through face to face interview, and the analysis of some selected news extracts that relates to xenophobic sentiment in South Africa. A total of 54 people were interviewed. The study reveals words used to refer to foreigners and that these words do no contribute to xenophobic sentiments in South Africa. Rather, xenophobic sentiments are caused by competition of limited available resources, theft, poverty, drugs related crimes, prostitution and human trafficking attributed to foreigners, as well as competition in the area of businesses. Keywords : Xenophobia, sentiments, attacks, discourse analysis, Sesotho, foreigner, negative attitude